Simple Configuration Effects on Eye Movements in Horizontal Scanning Tasks - Ilze Laicane; Jurgis Skilters; Ivars Lacis (Bern Open Publishing, 2015)
When reading text, observers alternate periods of stable gaze (fixations) and shifts of gaze (saccades). An important debate in the literature concerns the processes that drive the control of these eye movements. Past studies using strings of letters rather than meaningful text ('z-reading') suggest that eye movement control during reading is, to a large extent, controlled by low-level image properties. These studies, however, have failed to take into account perceptual grouping processes that could drive these low-level effects. We here study the role of various grouping factors in horizontal scanning eye movements, and compare these to reading meaningful text. The results show that sequential horizontal scanning of meaningless and visually distinctive stimuli is slower than for meaningful stimuli (e.g. letters instead of dots). Moreover, we found strong evidence for anticipatory processes in saccadic processing during horizontal scanning tasks. These results suggest a strong role of perceptual grouping in oculomotor control in reading.